Nutritional Analysis and Determination of Antioxidant Activity Using Free Radical Scavenging Assay of Potatoes (Solanum tuberosum) from Two Regions of Pakistan - Zahra, Naseem; Saeed, Muhammad Khalid; Nazir, Ashi; Ahmad, Ijaz; Nisa, Alim-un-; Hina, Sajila; Kalim, Imran (Biological Sciences - PJSIR, 2017)
Present study was designed to evaluate the nutritional values of red skin potatoes collected from Gujranwala and Lahore regions of Pakistan. Potatoes (Solanum tuberosum) of Gujranwala and Lahore were found to contain moisture contents of 5.00 and 5.15%, respectively. Fat was 0.19% in S. tuberosum of Gujranwala whereas Lahore potatoes were found to contain fat 0.2%. Fibre content of S. tuberosum of Gujranwala was 16.47% while S. tuberosum of Lahore had 13.45% fibre. Protein contents of S. tuberosum of Gujranwala were 12.89% whereas for S. tuberosum of Lahore were 13.11%. The water extract showed significant free radical scavenging activities in DPPH radical scavenging antioxidant assay and antioxidant activity was increased in a dose dependent manner. These results suggest that potato (S. tuberosum) is not only a cheap source of very important nutritents but also has antioxidant activities which are helpful to maintain different physiological functions of body.